Design and Development of a Lecturer Research Information System at Politeknik LP3I Pekanbaru - Desfita Eka Putri (CV Edujavare Publishing, 2026)
The development of information technology has a major impact on the speed and accuracy of data management in various fields, including lecturer research management. LP3I Pekanbaru Polytechnic experienced challenges in processing research data that were still manual and scattered, resulting in duplication of data, loss of research documents, and difficulty in monitoring research progress. This research aims to design and build an integrated, web-based, and Lecturer Research Information System that is able to support the efficient processing of research data. The research method used is Research and Development (R&D) with a Prototyping approach. The results of the research are in the form of an information system that includes research registration modules, fund submissions, progress monitoring, and publication of research results. The system also comes with a Use Case Diagram, Activity Diagram, and Sequence Diagram to support implementation. This system is expected to be able to improve the efficiency of lecturer research management and become an accurate and well-integrated research database.